Statistical Data Analysis of Weather Conditions Aiming at Determining the Mathematical Expectation of Construction Site Delays in Rijeka Within a Monthly Period (Proceedings of Faculty of Civil Engineering, 2019)
Meteorological and climate conditions can significantly affect the continuous and satisfactory progress of work on a construction site. When it comes to creating schedules and defining deadlines at a construction site it is very important to consider possible time delays during work execution as a result of adverse weather conditions. Still, this practice isn't widely applied.  Weather and climate conditions may have different effects depending on the location of the construction site. Hence, to be able to statistically analyze the effect of weather conditions in Rijeka area, with it's moderately warm and humid climate with hot summers (Cfa - Köppen climate classification), data on weather conditions that were measured and recorded in the central meteorological station in Rijeka during the period of last 25 years were requested from the Croatian Meteorological and Hydrological Service (DHMZ). The weather conditions the data was requested on are specific to the microclimate of the Rijeka area. They are as follows: precipitation (≥10 mm), storm winds, cold days (Tmin < 0 °C) and hot days (Tmax ≥ 30 °C). Requested meteorological data are in the form of the total number of days in a month with specific weather conditions recorded. The aim of this paper is to apply appropriate statistical tests in order to examine variations on the scale of significance of 5 % between distinct weather conditions (Kruskal-Wallis test, Mann-Whitney test), and to determine the 95% reliable interval of the mathematical expectation of work delays on a construction site for each month (an interval expectations assessment within a group containing normal data distribution). Monthly intervals obtained via statistical analysis that include mathematical expectation of execution delays due to poor weather condition represent a valuable input parameter for the purpose of creating a more precise schedule and defining construction deadlines in the Rijeka area.
Keywords: weather conditions; meteorological data; statistical analysis; delays; deadlines; schedules; Rijeka